Effects of supplementing a CP-reduced diet with rumen-protected methionine on Fleckvieh bull fattening - V. Inhuber; W. Windisch; B. Bächler; M. Schuster; H. Spiekers; T. Ettle (Animal, 2021)
The objective of this study was to evaluate the effect of supplementing a CP-reduced diet with rumen-protected methionine on growth performance of Fleckvieh bulls. A total of 69 bulls (367 ± 25 kg BW) were assigned to three feeding groups (n = 23 per group). The control (CON) diet contained 13.7% CP and 2.11 g methionine/kg diet (both DM basis) and was set as positive control. The diet reduced in CP (nitrogen) (RED) diet as negative control and the experimental RED + rumen-protected methionine (MET) diet were characterised by deficient CP concentrations (both 9.04% CP). The RED + MET diet differed from the RED diet in methionine concentration (2.54 g/kg DM vs. 1.56 g/kg DM, respectively) due to supplementation of rumen-protected methionine. Rumen-protected lysine was added to both RED and RED + MET at 2.7 g/kg DM to ensure a sufficient lysine supply relative to total and metabolisable protein intake. Metabolisable energy (ME) and nutrient composition were similar for CON, RED, and RED + MET. Bulls were fed for 105 days (d) on average. Individual feed intake was recorded daily; individual BW was recorded at the beginning of the experiment, once per month, and directly before slaughter. At slaughter, blood samples were collected and carcass traits were assessed. Reduction in dietary CP concentration reduced feed intake, and in combination with lower dietary CP concentration, daily intake of CP for RED and RED + MET was lower compared with CON (P < 0.01). Daily ME intake was reduced in RED and RED + MET compared with CON (P < 0.01). Consequently growth performance and carcass weights were reduced (both P < 0.01) in both RED and RED + MET compared with CON. Supplemental rumen-protected methionine was reflected in increased serum methionine concentration in RED + MET (P < 0.05) as compared to RED but it did not affect growth performance, carcass traits and serum amino acid (AA) concentrations, except for lysine which was reduced (P < 0.01) compared to CON and RED. In conclusion, bulls fed RED or RED + MET diets were exposed to a ruminal CP deficit and subsequently a deficit of prececal digestible protein, but methionine did not appear to be the first-limiting essential AA for growth under the respective experimental conditions.